HOW MUCH IS THE VALUE OF FOREST HYDROLOGICAL SERVICES FOR ELECTRICITY PRODUCTION: CASE STUDY AT HOA BINH HYDROPOWER RESERVOIR AREA - Van Dien, Pham (Journal of Forestry Science and Technology, 2016)
The importance of forests to provide hydrological services is well-known and has been widely documented. This is especially critical for hydroelectricity production where forests contribute to lower soil sedimentation and store water and thus maintain the capacity and prolong the longevity of hydroelectricity plants. However, the empirical evidence on measurable values of forest hydrological services is rare and controversial. We calculate the values of forest hydrological services for Hoa Binh Hydroelectricity Plant in Vietnam. Our valuation is based on the measurement of 240 permanent sample plots in different vegetations at watershed scale from 2001 to 2006, the manipulation with GIS and the simulation of the derived empirical models with different scenarios. Our findings indicate that total economic value of forest hydrological services for electricity production is currently 578.29 billion VND (26.29 million USD) per year and the longevity of the plant can be prolonged by 34.9 to 79.7 years depending on the forest cover in the watershed. Our findings can be used as the basis to identify the level of payment for forest hydrological services in Vietnam, which has been paid a special concern of scholars and policy-decision makers over the last years.